Samarium-cobalt permanent magnet and method for producing the same
Patent Information
- Application Number
- CN202510909171.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-20
- Filing Date
- 2025-07-02
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-07-02
AI Technical Summary
然而这些通过外加助剂或多种物料相互混合的方法,不仅会增加成本,同时难以保证能混合均匀,如添加氧化钐时容易团聚,加入超细粉氧化物后导致细晶粒集中分布等,导致磁体局部应力集中,致使磁体的磁性和力学性能一致性和稳定性降低
[0030]本发明所述的制备方法通过严格控制钐钴合金氧化热处理过程中的工艺条件,实现对氧化物含量及分布的调控,从而可以保障磁体在实现高抗弯强度的同时硬磁性能不被损害,并有效改善钐钴合金的成分偏析,进一步优化磁体的一致性和稳定性,进而,依靠高熔点氧化物对钐钴磁体进行晶粒细化并阻碍裂纹扩展,实现抗弯强度的大幅提升。此外,对氧化热处理后的钐钴合金进行制粉等工序,使氧化物均匀分散在磁体中,可以实现磁体中氧化物或细晶粒相对均匀的分布,有利于进一步增强磁体的磁性和力学性能一致性好、稳定性。
Smart Images

Figure CN120473326B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of permanent magnet manufacturing technology, and in particular to a samarium cobalt permanent magnet and its manufacturing method. Background Technology
[0002] As a second-generation rare-earth permanent magnet material, samarium cobalt permanent magnet material has significant advantages such as high Curie temperature, high magnetic energy product, excellent temperature stability and strong corrosion resistance. It is widely used in cutting-edge equipment in fields such as magnetic power, sensing and communication, and plays an irreplaceable role in aerospace, radar communication and defense industry.
[0003] However, due to the intrinsic crystal structure, strong magnetocrystalline anisotropy, orientation molding process, and internal stress and defects generated during sintering, rare earth permanent magnets suffer from poor strength and toughness. Samarium cobalt permanent magnets, in particular, exhibit cleavage brittle fracture, with a bending strength typically only 80MPa-120MPa. This makes them prone to cracking and chipping during processing, significantly reducing yield and processing accuracy, increasing manufacturing costs, and limiting their application in high-precision, vibration-resistant, and impact-resistant fields.
[0004] Existing technologies improve mechanical strength by pre-oxidizing ultrafine powders (0.01μm-2μm) to achieve an oxygen content as high as 4000ppm-10000ppm, and then mixing them with conventional powders in a specific ratio. However, these methods, which involve adding additives or mixing multiple materials, not only increase costs but also make it difficult to ensure uniform mixing. For example, adding samarium oxide can easily lead to agglomeration, and adding ultrafine oxide powder can cause fine grains to concentrate, resulting in localized stress concentration in the magnet and reducing the consistency and stability of the magnet's magnetic and mechanical properties.
[0005] Therefore, how to improve the strength and toughness of samarium cobalt permanent magnets while ensuring their high hardness and magnetic properties has become an urgent and important problem. Summary of the Invention
[0006] Therefore, it is necessary to provide a samarium cobalt permanent magnet and its preparation method to address the above problems. The preparation method can significantly improve the bending strength while ensuring the high hardness magnetic properties of the samarium cobalt permanent magnet. The preparation process is simple and efficient and suitable for industrial production.
[0007] A method for preparing a samarium cobalt permanent magnet includes the following steps:
[0008] Samarium-cobalt alloys are available.
[0009] The samarium-cobalt alloy is subjected to an oxidation heat treatment, and the oxidation heat treatment process satisfies the following relationship: t=kP / T, where t is the holding time in hours; T is the heating temperature in °C; P is the vacuum degree in Pa; and k is a coefficient, k=100-5000.
[0010] The samarium-cobalt alloy after oxidation heat treatment was crushed and powdered to obtain alloy powder.
[0011] After the alloy powder is oriented and shaped to obtain a samarium-cobalt green blank, a samarium-cobalt permanent magnet is obtained by sintering.
[0012] In one embodiment, the heating temperature T is 300℃-1200℃;
[0013] And / or, the vacuum degree P is 0.1 Pa to 20 Pa.
[0014] In one embodiment, when P ≥ 10 Pa, 100 ≤ k ≤ 300, and 300℃ ≤ T < 600℃;
[0015] Alternatively, when 5Pa≤P<10Pa, 200 <k≤500,500℃<T<800℃;
[0016] Alternatively, when 1Pa≤P<5Pa, 400 <k≤800,700℃<T<1000℃;
[0017] Alternatively, when 0.1Pa ≤ P < 1Pa, 800 <k≤3000,900℃<T≤1200℃。
[0018] In one embodiment, the samarium-cobalt alloy comprises: 23%-28% Sm, 13%-25% Fe, 4%-10% Cu, 1.5%-3.5% Zr, and the balance Co.
[0019] In one embodiment, the thickness of the oxide layer on the surface of the samarium-cobalt alloy after oxidation heat treatment is 1 μm-5 μm;
[0020] And / or, the oxygen content of the samarium-cobalt alloy after oxidation heat treatment is 1500ppm-4000ppm.
[0021] In one embodiment, the coarse particles obtained by the crushing process have a particle size of less than 5 mm;
[0022] And / or, the alloy powder has a specific surface area average particle size of 3μm-8μm and a maximum particle size of less than or equal to 35μm.
[0023] In one embodiment, during the orientation forming step, the magnetic field strength is greater than or equal to 2T;
[0024] And / or, the density of the samarium cobalt green compact is 4.5 g / cm³. 3 -5.5g / cm 3 .
[0025] In one embodiment, the sintering treatment includes sintering solution treatment, the process of which includes: pre-sintering by heating to 1130℃-1180℃ at a heating rate of 0.5℃ / min-10℃ / min and holding for 0.5h-5h under vacuum conditions less than or equal to 0.05Pa; then sintering by heating to 1170℃-1240℃ in an inert gas environment and holding for 1h-8h; then solution treatment by cooling to 1110℃-1180℃ at a cooling rate of 0.2℃ / min-5℃ / min and holding for 2h-72h; and finally, rapid quenching to below 400℃ at a cooling rate of 40℃ / min-200℃ / min after solution treatment.
[0026] And / or, the sintering treatment further includes tempering aging, the tempering aging process comprising: heating to 750℃-900℃ at a heating rate of 0.5℃ / min-10℃ / min and holding for 1h-50h in an inert gas environment or under vacuum conditions ≤0.1Pa, and then cooling to 300℃-500℃ at a cooling rate of 0.1℃ / min-1℃ / min and holding for 1h-30h.
[0027] A samarium cobalt permanent magnet, wherein the samarium cobalt permanent magnet is prepared by the preparation method described above, and the oxygen content of the samarium cobalt permanent magnet is 3500ppm-6000ppm.
[0028] In one embodiment, the average grain size of the samarium cobalt permanent magnet is 30 μm-80 μm;
[0029] And / or, the maximum grain size of the samarium cobalt permanent magnet is less than 170 μm.
[0030] The preparation method described in this invention achieves control over the oxide content and distribution during the oxidation heat treatment of samarium-cobalt alloy by strictly controlling the process conditions. This ensures that the magnet achieves high bending strength without compromising its hard magnetic properties, effectively improves the compositional segregation of the samarium-cobalt alloy, and further optimizes the magnet's consistency and stability. Furthermore, the high-melting-point oxides refine the grain size of the samarium-cobalt magnet and inhibit crack propagation, resulting in a significant increase in bending strength. In addition, the powdering process after oxidation heat treatment of the samarium-cobalt alloy ensures that the oxides are uniformly dispersed in the magnet, achieving a relatively uniform distribution of oxides or fine grains. This further enhances the magnet's magnetic and mechanical properties, ensuring good consistency and stability.
[0031] Therefore, the preparation method described in this invention not only successfully achieves a balance between the high hardness and high bending strength of samarium cobalt permanent magnets, but also eliminates the need to add external additives or materials to the samarium cobalt alloy. The preparation method is simple, efficient, and suitable for industrial production. Attached Figure Description
[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 The image shows a scanning electron microscope (SEM) image of the cross-section of the samarium-cobalt alloy obtained in Example 1 after oxidation.
[0034] Figure 2 Metallographic photograph of the samarium cobalt permanent magnet prepared in Example 1;
[0035] Figure 3 Metallographic photograph of the samarium cobalt permanent magnet prepared for Comparative Example 1;
[0036] Figure 4 The image shows a scanning electron microscope (SEM) image of the cross-section of the samarium-cobalt alloy prepared in Comparative Example 3 after oxidation.
[0037] Figure 5 Metallographic photograph of the samarium cobalt permanent magnet prepared for Comparative Example 4. Detailed Implementation
[0038] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0040] This invention provides a method for preparing a samarium cobalt permanent magnet, comprising the following steps:
[0041] S1 provides samarium-cobalt alloy;
[0042] S2, the samarium-cobalt alloy is subjected to an oxidation heat treatment, and the oxidation heat treatment process satisfies the following relationship: t=kP / T, where t is the holding time in hours; T is the heating temperature in °C; P is the vacuum degree in Pa; and k is a coefficient, k=100-5000;
[0043] S3, the samarium-cobalt alloy after oxidation heat treatment is crushed and powdered to obtain alloy powder;
[0044] S4. After the alloy powder is oriented and shaped to obtain a samarium-cobalt green blank, a samarium-cobalt permanent magnet is obtained by sintering.
[0045] The present invention does not limit the samarium cobalt alloy used in step S1. Existing samarium cobalt alloys can be used. Alternatively, the raw material metal can be poured into a crucible for induction melting, and after being melted into molten steel, it can be poured into a water-cooled mold to prepare a master alloy ingot.
[0046] In one embodiment, the samarium-cobalt alloy comprises: 23%-28% Sm, 13%-25% Fe, 4%-10% Cu, 1.5%-3.5% Zr, and the balance Co.
[0047] In step S2, by strictly controlling the process conditions during the oxidation heat treatment of samarium-cobalt alloy, the content and distribution of oxides are regulated, thereby ensuring that the magnet achieves high bending strength without damaging its hard magnetic properties. This also effectively improves the compositional segregation of the samarium-cobalt alloy, further optimizing the consistency and stability of the magnet. Furthermore, by relying on high-melting-point oxides to refine the grains of the samarium-cobalt magnet and inhibit crack propagation, a significant improvement in bending strength is achieved.
[0048] It should be noted that the relationship in the described oxidation heat treatment process is only a quantitative conversion and does not involve unit conversion.
[0049] Preferably, the heating temperature T is 300℃-1200℃, including but not limited to any one or any two of the following values: 300℃, 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃, 1100℃, and 1200℃.
[0050] Preferably, the vacuum degree P is 0.1Pa-20Pa, including but not limited to any one or any two of the following values: 0.1Pa, 0.5Pa, 1Pa, 5Pa, 10Pa, 15Pa, and 20Pa.
[0051] In one embodiment, when P≥10Pa, 100≤k≤300, 300°C≤T<600°C. Preferably, when 10Pa≤P<20Pa, 100≤k≤200, 500°C≤T<600°C.
[0052] In one embodiment, when 5Pa≤P<10Pa, 200<k≤500, 500°C<T<800°C. Preferably, 600°C≤T<800°C.
[0053] In one embodiment, when 1Pa≤P<5Pa, 400<k≤800, 700°C<T<1000°C. Preferably, when 1Pa≤P<5Pa, 500<k≤800, 800°C≤T≤900°C.
[0054] In one embodiment, when 0.1Pa≤P<1Pa, 800<k≤3000, 900°C<T≤1200°C.
[0055] In one embodiment, the thickness of the surface oxide layer of the samarium-cobalt alloy after oxidative heat treatment is 1μm to 5μm, including but not limited to any one point value selected from 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 4μm and 5μm, or a range value formed by any two of the point values.
[0056] In one embodiment, the oxygen content of the samarium-cobalt alloy after oxidative heat treatment is 1500ppm to 4000ppm, including but not limited to any one point value selected from 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm and 4000ppm, or a range value formed by any two of the point values.
[0057] In step S3, the samarium-cobalt alloy after oxidative heat treatment is subjected to processes such as powder preparation to uniformly disperse the oxide in the magnet, which can realize relatively uniform distribution of oxides or fine grain phases in the magnet, and is conducive to further enhancing the magnetic properties, consistency of mechanical properties and stability of the magnet.
[0058] In one embodiment, the crushing process includes but is not limited to mechanical crushing, and mechanical crushing is preferred in the present invention.
[0059] In one embodiment, the particle size of the coarse particles obtained by crushing is less than 5mm.
[0060] In one embodiment, the powder preparation process includes but is not limited to jet milling or ball milling.
[0061] In one embodiment, the specific surface average particle size (SMD) of the alloy powder is 3μm to 8μm, and the maximum particle size in the alloy powder is less than or equal to 35μm.
[0062] The present invention does not limit the orientation forming and sintering process used in step S4, and existing processes can be used.
[0063] In one embodiment, the orientation forming process includes: orienting alloy powder under the action of a magnetic field, and further forming it by isostatic pressing to obtain a samarium cobalt green blank.
[0064] Preferably, the magnetic field strength for the orientation forming is greater than or equal to 2T; the density of the compact after magnetic orientation forming is preferably 3.5 g / cm³. 3 -4.5g / cm 3 The preferred density of the samarium cobalt green compact obtained after isostatic pressing is 4.5 g / cm³. 3 -5.5g / cm 3 .
[0065] In one embodiment, the sintering process includes sintering solution treatment and tempering aging, wherein the sintering solution treatment includes: oxygen-free sintering of samarium cobalt green blanks, followed by solution treatment after sintering to achieve density, and rapid quenching and cooling after solution treatment.
[0066] Preferably, the sintering and solution treatment process specifically includes the following steps: under a vacuum degree less than or equal to 0.05 Pa, the temperature is raised to 1130℃-1180℃ at a heating rate of 0.5℃ / min-10℃ / min and held for 0.5h-5h for pre-sintering; then, the temperature is raised to 1170℃-1240℃ in an inert gas environment and held for 1h-8h for sintering; then, the temperature is lowered to 1110℃-1180℃ at a cooling rate of 0.2℃ / min-5℃ / min and held for 2h-72h for solution treatment; after the solution treatment, the temperature is rapidly quenched to below 400℃ at a cooling rate of 40℃ / min-200℃ / min.
[0067] It should be noted that the present invention does not limit the processing of each stage in the above-mentioned sintering and solution treatment process to one or more steps. For example, in the pre-sintering process, it can be heated to 300°C and held for 1 hour, then heated to 800°C and held for 1.5 hours, and then heated to the pre-sintering temperature, or it can be directly heated to the pre-sintering temperature; in the solution treatment process, it can be cooled to 1170°C and held for 2 hours, then cooled to 1150°C and held for 4 hours, then cooled to 1130°C and held for 10 hours, or it can be directly cooled to the solution temperature.
[0068] In one embodiment, the tempering aging process preferably includes the following steps: heating to 750℃-900℃ at a heating rate of 0.5℃ / min-10℃ / min and holding for 1h-50h in an inert gas environment or under vacuum conditions ≤0.1Pa, and then cooling to 300℃-500℃ at a cooling rate of 0.1℃ / min-1℃ / min and holding for 1h-30h.
[0069] It should be noted that the present invention does not limit the processing of each stage in the above-mentioned tempering and aging process to one step or multiple steps. For example, in the heating process, it can be heated to 300°C and held for 1 hour, then heated to 600°C and held for 2 hours, and then heated to the first-stage aging temperature, or it can be heated to the tempering temperature in one step; in the cooling process, it can be cooled to 700°C and held for 2 hours, then cooled to 600°C and held for 4 hours, and then cooled to the final aging temperature, or it can be cooled to the second-stage aging temperature in one step.
[0070] Therefore, the preparation method described in this invention not only successfully achieves a balance between the high hardness and high bending strength of samarium cobalt permanent magnets, but also eliminates the need to add external additives or materials to the samarium cobalt alloy. The preparation method is simple, efficient, and suitable for industrial production.
[0071] The present invention also provides a samarium cobalt permanent magnet, which is prepared by the preparation method described above. The oxygen content of the samarium cobalt permanent magnet is 3500ppm-6000ppm, including but not limited to any one or any two of the following values: 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, and 6000ppm.
[0072] In one embodiment, the average grain size of the samarium cobalt permanent magnet is 30μm-80μm, including but not limited to any one or any two of the following values: 30μm, 40μm, 50μm, 60μm, 70μm, and 80μm.
[0073] In one embodiment, the maximum grain size of the samarium cobalt permanent magnet is less than 170 μm, including but not limited to any one or any two of the following values: 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, and 150 μm.
[0074] The samarium-cobalt permanent magnet and its preparation method will be further described below through specific embodiments. However, those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified, specific conditions in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0075] Example 1
[0076] A total of 100 kg of raw material metal was prepared by induction melting, consisting of 25% Sm, 17% Fe, 5% Cu, 3% Zr, and the balance Co. The ingot was then oxidized and heat-treated: heated to 1000 °C and held for 1 hour under a vacuum of 0.5 Pa, followed by cooling to room temperature. The cross-section of the oxidized samarium-cobalt alloy ingot was characterized by scanning electron microscopy (SEM). Figure 1 As shown, the oxide layer thickness of the ingot is approximately 3.5 μm, and the overall oxygen content of the ingot is further measured to be 2684 ppm.
[0077] The ingots were then mechanically crushed into coarse particles smaller than 1 mm, and then processed by air jet milling to produce powder with a surface area ratio (SMD) of 4.35 μm and a maximum particle size not exceeding 23.41 μm. The powder was then uniformly mixed using a three-dimensional mixer. The mixed fine powder was then oriented and shaped in a 2T magnetic field, resulting in a compact density of 4.2 g / cm³. 3 Subsequently, it was isostatically pressed at 230 MPa for 30 min to obtain a density of 5.0 g / cm³. 3 The raw clay.
[0078] The green blank was placed in a sintering furnace, and the vacuum was reduced to below 0.01 Pa. The temperature was then increased to 450°C at a heating rate of 2°C / min and held for 2 hours. Next, the temperature was increased to 950°C at a heating rate of 3°C / min and held for 2 hours. Finally, the temperature was increased to 1150°C at a heating rate of 3.33°C / min and held for 1 hour for pre-sintering. Argon gas was then introduced, and the temperature was increased to 1200°C at a heating rate of 0.83°C / min and held for 3 hours for sintering. After sintering, the temperature was decreased to 1180°C at a cooling rate of 1°C / min and held for 4 hours for solution treatment. After solution treatment, the temperature was rapidly cooled to room temperature at a cooling rate of 65°C / min to obtain the sintered blank.
[0079] Subsequently, the sintered blank was heated to 650°C at a heating rate of 10°C / min and held for 1 hour in a vacuum environment of less than 0.1 Pa. Then, it was heated to 810°C at a heating rate of 2°C / min and held for 10 hours for primary aging. Then, it was slowly cooled to 400°C at a cooling rate of 0.7°C / min and held for 4 hours for secondary aging. Finally, it was cooled to room temperature in the furnace and removed from the furnace to obtain samarium cobalt permanent magnets.
[0080] The prepared samarium-cobalt permanent magnets were characterized by metallography, and the results are as follows: Figure 2 As shown, the average grain size of the magnet is 62.8 μm, the maximum size is 136 μm, the oxygen content of the magnet is 4316 ppm, and the oxide (white substance in the metallographic image) is relatively uniformly dispersed in the magnet.
[0081] Example 2
[0082] A total of 40 kg of raw material metal was prepared by induction melting, consisting of 24.8% Sm, 19.3% Fe, 5% Cu, 2.7% Zr, and the balance Co. The resulting ingot was then prepared. The ingot underwent an oxidation heat treatment: it was heated to 550℃ at 12 Pa and held for 3.5 h, then cooled to room temperature. The oxide layer thickness was measured to be approximately 2.8 μm, and the overall oxygen content was 2210 ppm.
[0083] The ingots were then mechanically crushed into coarse particles smaller than 1 mm, followed by air jet milling and ball milling to prepare powders with a surface area ratio (SMD) of 4.58 μm and 3.95 μm, respectively, and a maximum particle size not exceeding 23.41 μm. The powders were then uniformly mixed using a three-dimensional mixer. The mixed fine powder was then oriented and shaped in a 2T magnetic field, resulting in a compact density of 4.0 g / cm³. 3 Subsequently, it was isostatically pressed at 250 MPa for 30 min to obtain a density of 5.1 g / cm³. 3 The raw clay.
[0084] The green blanks were placed in a sintering furnace, and the vacuum was reduced to below 0.01 Pa. The temperature was increased to 300℃ at a heating rate of 2℃ / min and held for 2 hours, then increased to 850℃ at a heating rate of 3.5℃ / min and held for 2 hours, then increased to 1000℃ at a heating rate of 2.5℃ / min and held for 1 hour, and then increased to 1180℃ at a heating rate of 3℃ / min and held for 1 hour for pre-sintering. Argon gas was then introduced, and the temperature was increased to 1195℃ at a heating rate of 0.83℃ / min and held for 2.5 hours for sintering. After sintering, the temperature was decreased to 1175℃ at a cooling rate of 1℃ / min and held for 2 hours, then decreased to 1165℃ at a cooling rate of 0.7℃ / min and held for 4 hours, and finally decreased to 1160℃ at a cooling rate of 0.7℃ / min and held for 12 hours for solution treatment. After solution treatment, the sample is rapidly cooled to room temperature at a cooling rate of 80℃ / min to obtain a sintered blank.
[0085] Subsequently, the sintered blank was heated to 600°C at a heating rate of 10°C / min and held for 1 hour in a vacuum environment of less than 0.1 Pa. Then, it was heated to 820°C at a heating rate of 2°C / min and held for 15 hours for primary aging. Then, it was slowly cooled to 400°C at a cooling rate of 0.5°C / min and held for 6 hours for secondary aging. Finally, it was cooled to room temperature in the furnace and removed from the furnace to obtain samarium cobalt permanent magnets.
[0086] Example 3
[0087] 100 kg of raw material metal was prepared by induction melting, consisting of 24.8% Sm, 23% Fe, 5% Cu, 2.5% Zr, and the balance Co. The resulting ingot was then prepared. The ingot underwent oxidation heat treatment: it was heated to 750°C and held for 3.2 h under a vacuum of 8 Pa, followed by cooling to room temperature. The oxide layer thickness was measured to be approximately 4.6 μm, and the overall oxygen content was 3413 ppm.
[0088] The cast sheets were then mechanically crushed into coarse particles smaller than 2 mm, and then processed by air jet milling to produce powder with a specific surface area average (SMD) of 4.14 μm and a maximum particle size not exceeding 21.67 μm. The powder was then uniformly mixed using a three-dimensional mixer. The mixed fine powder was then oriented and shaped in a 2T magnetic field, resulting in a compact density of 3.8 g / cm³. 3 Subsequently, it was isostatically pressed at 250 MPa for 45 min to obtain a density of 5.1 g / cm³. 3 The raw clay.
[0089] The green blanks were placed in a sintering furnace, and the vacuum was reduced to below 0.01 Pa. The temperature was increased to 300℃ at a heating rate of 2℃ / min and held for 2 hours, then increased to 850℃ at a heating rate of 3.5℃ / min and held for 2 hours, then increased to 1000℃ at a heating rate of 2.5℃ / min and held for 1 hour, and then increased to 1180℃ at a heating rate of 3℃ / min and held for 1 hour for pre-sintering. Argon gas was then introduced, and the temperature was increased to 1193℃ at a heating rate of 0.83℃ / min and held for 2.5 hours for sintering. After sintering, the temperature was decreased to 1160℃ at a cooling rate of 1℃ / min and held for 2 hours, then decreased to 1150℃ at a cooling rate of 1℃ / min and held for 8 hours, and finally decreased to 1140℃ at a cooling rate of 0.7℃ / min and held for 15 hours for solution treatment. After solution treatment, the sample is rapidly cooled to room temperature at a cooling rate of 80℃ / min to obtain a sintered blank.
[0090] Subsequently, the sintered blank was heated to 600°C at a heating rate of 10°C / min and held for 1 hour in a vacuum environment of less than 0.1 Pa. Then, it was heated to 810°C at a heating rate of 2°C / min and held for 20 hours for primary aging. Then, it was slowly cooled to 400°C at a cooling rate of 0.3°C / min and held for 10 hours for secondary aging. Finally, it was cooled to room temperature in the furnace and removed from the furnace to obtain the final samarium cobalt magnet.
[0091] Example 4
[0092] A total of 40 kg of raw material metal was prepared by induction melting, consisting of 25% Sm, 21.5% Fe, 5% Cu, 3% Zr, and the balance Co. The resulting ingot was then prepared. The ingot underwent an oxidation heat treatment: it was heated to 800℃ at 2 Pa and held for 1.5 h, then cooled to room temperature. The oxide layer thickness was measured to be approximately 2.5 μm, and the overall oxygen content was 1897 ppm.
[0093] The ingots were then mechanically crushed into coarse particles smaller than 1 mm, followed by air jet milling and ball milling to prepare powders with a specific surface area average (SMD) of 4.5 μm and 4.0 μm, respectively, and a maximum particle size not exceeding 23.66 μm. The powders were then uniformly mixed using a three-dimensional mixer. The mixed fine powder was then oriented and shaped in a 2.3T magnetic field, resulting in a compact density of 4.15 g / cm³. 3 Subsequently, it was isostatically pressed at 250 MPa for 30 min to obtain a density of 5.1 g / cm³. 3 The raw clay.
[0094] The green blanks were placed in a sintering furnace, and the vacuum was reduced to below 0.01 Pa. The temperature was increased to 300℃ at a heating rate of 2℃ / min and held for 2 hours, then increased to 850℃ at a heating rate of 3.5℃ / min and held for 2 hours, then increased to 1000℃ at a heating rate of 2.5℃ / min and held for 1 hour, and then increased to 1180℃ at a heating rate of 3℃ / min and held for 1 hour for pre-sintering. Argon gas was then introduced, and the temperature was increased to 1195℃ at a heating rate of 0.83℃ / min and held for 2.5 hours for sintering. After sintering, the temperature was decreased to 1175℃ at a cooling rate of 1℃ / min and held for 2 hours, then decreased to 1165℃ at a cooling rate of 0.7℃ / min and held for 4 hours, and finally decreased to 1160℃ at a cooling rate of 0.7℃ / min and held for 12 hours for solution treatment. After solution treatment, the sample is rapidly cooled to room temperature at a cooling rate of 80℃ / min to obtain a sintered blank.
[0095] Subsequently, the sintered blank was heated to 600°C at a heating rate of 10°C / min and held for 1 hour in a vacuum environment of less than 0.1 Pa. Then, it was heated to 820°C at a heating rate of 2°C / min and held for 15 hours for primary aging. Then, it was slowly cooled to 400°C at a cooling rate of 0.5°C / min and held for 6 hours for secondary aging. Finally, it was cooled to room temperature in the furnace and removed from the furnace to obtain samarium cobalt permanent magnets.
[0096] Comparative Example 1
[0097] The difference between Comparative Example 1 and Example 1 is that no oxidation heat treatment was performed on the ingot, resulting in an ingot with an overall oxygen content of 427 ppm and a magnet oxygen content of 2568 ppm. The magnet metallographic structure is as follows: Figure 3As shown, its average grain size is 85.3 μm, the maximum grain size is 194 μm, and the oxide distribution is significantly lower than that of the magnet in Example 1. The magnetic properties are remanence Br = 11.21 kGs, intrinsic coercivity Hcj = 28.78 kOe, and maximum energy product (BH)max = 31.05 MGOe. It can be seen that the magnetic properties are similar to those of the magnet in Example 1, but the bending strength is only 117 MPa.
[0098] Comparative Example 2
[0099] The difference between Comparative Example 2 and Example 2 is that the ingot was subjected to an oxidation heat treatment: the ingot was heated to 100°C at 12 Pa and held for 1.5 h, and then cooled to room temperature. The overall oxygen content of the ingot was measured to be 1098 ppm, and the oxygen content of the magnet was 2688 ppm.
[0100] Comparative Example 3
[0101] The difference between Comparative Example 3 and Example 1 is that the ingot underwent an oxidative heat treatment: the ingot was heated to 1000°C and held for 2 hours under a vacuum of 30 Pa, then cooled to room temperature. The cross-section of the ingot was characterized by scanning electron microscopy (SEM), and the results are as follows. Figure 4 As shown, the oxide layer thickness of the ingot is approximately 5.8 μm. Further measurements revealed that the overall oxygen content of the ingot was 5238 ppm, and the oxygen content of the magnet was 9897 ppm.
[0102] Comparative Example 4
[0103] The difference between Comparative Example 4 and Comparative Example 1 is that a suitable amount of Comparative Example 1 powder was taken, and 3 wt% samarium oxide was added. The mixture was then uniformly mixed, pressed, sintered, dissolved, and tempered to obtain a magnet. The oxygen content of the magnet was 2787 ppm, which is close to that of Comparative Example 1. Metallographic characterization of the magnet was performed, and the results are as follows... Figure 5 As shown, samarium oxide (the white substance in the figure) exhibits agglomeration, with localized concentration of fine grains.
[0104] The preparation parameters for Examples 1-4 and Comparative Examples 1-4 are shown in Table 1.
[0105] Table 1
[0106]
[0107] The magnetic properties of the magnets prepared in Examples 1-4 and Comparative Examples 1-4 were measured, and the bending strength was measured in accordance with the standard "Test Methods for Physical Properties of Rare Earth Permanent Magnet Materials Part 2: Determination of Bending Strength and Fracture Toughness" (GB / T 31967.2-2015). The results are shown in Table 2.
[0108] Table 2
[0109]
[0110] As shown in Examples 1-4 of Table 2, under different raw material ratios, the samarium cobalt permanent magnets prepared by the method described in this invention can simultaneously possess both high hard magnetic properties and high bending strength. The samarium cobalt permanent magnet prepared in Comparative Example 1 has a remanence of 11.21 kGs, an intrinsic coercivity of 28.78 kOe, and a maximum energy product of 31.05 MGOe. Under the same raw material ratio, although its magnetic properties are similar to those of Example 1, its bending strength is only 117 MPa. The samarium cobalt permanent magnet prepared in Comparative Example 2 has a remanence of 11.61 kGs, an intrinsic coercivity of 26.13 kOe, and a maximum energy product of 32.01 MGOe. Under the same raw material ratio, although its magnetic properties are similar to those of Example 2, its bending strength is only 122 MPa. In Comparative Example 3, the excessively high oxygen content leads to a significant decrease in the hard magnetic properties of the magnet. In Comparative Example 4, since samarium oxide is a non-magnetic material, its agglomeration not only reduces the consistency and stability of the magnetic properties of the magnet, but also affects the mechanical properties due to local stress concentration. As a result, under the same raw material ratio, the bending strength is reduced by 11 MPa compared with Example 1.
[0111] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0112] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a samarium-cobalt permanent magnet, characterized in that, The preparation method comprises the following steps: providing a samarium-cobalt alloy; subjecting the samarium-cobalt alloy to oxidative heat treatment, wherein the process of the oxidative heat treatment satisfies the following relational expression: t=kP / T, where t is the holding time in h; T is the heating temperature in °C; P is the vacuum degree in Pa; k is a coefficient with k=100-5000; the heating temperature T is 300°C-1200°C, and the vacuum degree P is 0.1Pa-20Pa; when P≥10Pa, 100≤k≤300, 300°C≤T<600°C; or, when 5Pa≤P<10Pa, 200<k≤500, 500°C<T<800°C; or, when 1Pa≤P<5Pa, 400<k≤800, 700°C<T<1000°C; or, when 0.1Pa≤P<1Pa, 800<k≤3000, 900°C<T≤1200°C; crushing and pulverizing the samarium-cobalt alloy after the oxidative heat treatment to obtain alloy powder; subjecting the alloy powder to orientation forming to obtain a samarium-cobalt green body, and then performing sintering treatment to produce a samarium-cobalt permanent magnet.
2. The method for preparing a samarium-cobalt permanent magnet according to claim 1, characterized in that, The components of the samarium-cobalt alloy include: 23%-28% Sm, 13%-25% Fe, 4%-10% Cu, 1.5%-3.5% Zr, and the balance Co.
3. The method for preparing a samarium-cobalt permanent magnet according to claim 1, characterized in that, The thickness of the surface oxide layer of the samarium-cobalt alloy after the oxidative heat treatment is 1μm-5μm; and / or, the oxygen content of the samarium-cobalt alloy after the oxidative heat treatment is 1500ppm-4000ppm.
4. The method for preparing a samarium-cobalt permanent magnet according to claim 1, characterized in that, The particle size of the coarse particles obtained by crushing is less than 5mm; and / or, the specific surface average particle size of the alloy powder is 3μm-8μm, and the maximum particle size is less than or equal to 35μm.
5. The method for preparing a samarium-cobalt permanent magnet according to claim 1, characterized in that, In the orientation forming step, the magnetic field strength is greater than or equal to 2T; And / or, the density of the samarium cobalt green compact is 4.5 g / cm³. 3 -5.5g / cm 3 .
6. The method for preparing a samarium-cobalt permanent magnet according to claim 1, characterized in that, The sintering treatment includes sintering solution treatment, and the process of the sintering solution treatment comprises: under the condition that the vacuum degree is less than or equal to 0.05Pa, heating up to 1130°C-1180°C at a heating rate of 0.5°C / min-10°C / min and holding for 0.5h-5h for pre-sintering, then heating up to 1170°C-1240°C in an inert gas atmosphere and holding for 1h-8h for sintering, then cooling down to 1110°C-1180°C at a cooling rate of 0.2°C / min-5°C / min and holding for 2h-72h for solution treatment, and after the solution treatment is completed, performing rapid quenching to below 400°C at a cooling rate of 40°C / min-200°C / min; and / or, the sintering treatment further includes tempering aging, and the process of the tempering aging comprises: in an inert gas atmosphere or under the condition that the vacuum degree is ≤0.1Pa, heating up to 750°C-900°C at a heating rate of 0.5°C / min-10°C / min and holding for 1h-50h, then cooling down to 300°C-500°C at a cooling rate of 0.1°C / min-1°C / min and holding for 1h-30h.
7. A samarium-cobalt permanent magnet, characterized in that, The samarium-cobalt permanent magnet is prepared by the preparation method according to any one of claims 1 to 6, and the oxygen content of the samarium-cobalt permanent magnet is 3500ppm-6000ppm.
8. The samarium-cobalt permanent magnet according to claim 7, characterized in that, The average grain size of the samarium cobalt permanent magnet is 30μm-80μm; And / or, the maximum grain size of the samarium cobalt permanent magnet is less than 170 μm.
Citation Information
Patent Citations
Method for producing soft magnetic metal powder coated with Mg-containing oxide film and method for producing composite soft magnetic material from the powder
CN101056729A
Manufacturing method of 550 DEG C high-temperature-resistant samarium-cobalt permanent magnet material
CN112435846A
